2015
DOI: 10.1111/acel.12321
|View full text |Cite
|
Sign up to set email alerts
|

A peroxiredoxin,PRDX‐2, is required for insulin secretion and insulin/IIS‐dependent regulation of stress resistance and longevity

Abstract: Peroxiredoxins (Prx) are abundant thiol peroxidases with a conserved anti-ageing role. In contrast to most animals, the nematode worm, Caenorhabditis elegans, encodes a single cytosolic 2-Cys Prx, PRDX-2, rendering it an excellent model for examining how peroxiredoxins affect animal physiology and ageing. Our previous work revealed that, although PRDX-2 protects against the toxicity of peroxides, enigmatically, prdx-2-mutant animals are hyper-resistant to other forms of oxidative stress. Here, we have investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…Likewise, several studies of regulation by low levels of ROS identified peroxidases that act in homeostasis as ROS sensors rather than ROS quenchers. For example, the knockout of peroxiredoxin-2 showed that the protein is required for normal levels of insulin secretion in Caenorhabditis elegans (Olahova and Veal, 2015), and the knockout of glutathione peroxidase-1 resulted in improved glucose control in mice (Merry et al, 2016). Intriguingly, regulation by low levels of ROS displays special attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies of regulation by low levels of ROS identified peroxidases that act in homeostasis as ROS sensors rather than ROS quenchers. For example, the knockout of peroxiredoxin-2 showed that the protein is required for normal levels of insulin secretion in Caenorhabditis elegans (Olahova and Veal, 2015), and the knockout of glutathione peroxidase-1 resulted in improved glucose control in mice (Merry et al, 2016). Intriguingly, regulation by low levels of ROS displays special attributes.…”
Section: Discussionmentioning
confidence: 99%
“…SKN-1 also up-regulates expression of two genes that encode glutathione peroxidases. DAF-16 and SKN-1 are also associated with the up-regulation of the PRDX-2 gene that encodes peroxiredoxin in C. elegans (Oláhová and Veal, 2015). Comparative genomics studies have enabled ROS-scavenging enzymes to be identified in PPNs (Abad et al , 2008; Opperman et al , 2008; Bird et al , 2009).…”
Section: Section Ii: Potential Key Regulators Of Oxidative Stress Resmentioning
confidence: 99%
“…In agreement with www.nature.com/scientificreports www.nature.com/scientificreports/ this hypothesis, we have confirmed that downregulation of the MiDaf16-like and MiSkn1-like1 genes results in strong downregulation of genes from their networks during parasitism of M. incognita in single-or double-gene silencing plants. In this respect, the two superoxide dismutases (MiSod1-like1 and MiSod3-like1), peroxiredoxin (MiPRDX2-like1), glutathione S-transferase and peroxidase (MiGst1-like1 and MiGPX-like1), which act in the nematode antioxidant and detoxification pathways [18][19][20]63,64 , were indeed downregulated in M. incognita during parasitism in transgenic plants.…”
Section: Discussionmentioning
confidence: 96%